Optimality conditions for circular cone complementarity programs. (4th March 2022) - Thinh, V. D.; Chuong, T. D.; Anh, N. L. H.
Abstract : In this paper, we first provide some results on first- and second-order analysis to a circular cone complementary set Γ. In this way, we obtain a parabolical regularity of Γ as well as an exact computation for second epi-derivative of the indicator function to Γ. We then establish first- and second-order optimality conditions for a mathematical programming problem involving a circular cone complementary constraint under the validation of metric subregularity and second-order tangent constraint qualification. Our results are sharpened in comparison with some existing ones in the literature.